Pengaruh Struktur Modal, Profitabilitas dan Kebijakan Dividen Terhadap Nilai Perusahaan pada Perusahaan Sektor Basic Materials di BEI Periode 2019-2023 - Elsaday Br Silalahi, Ruth; Gultom , Robinhot; Melianna, Saur (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This research aims to determine the Influence of Capital Structure, Profitability, and Dividend Policy on Company Value in Basic Materials Sector Companies listed on the Indonesia Stock Exchange for the 2019-2023 Period. The variables used in this study, the independent variable (X) consists of capital structure proxied by Debt to Equity Ratio, Profitability proxied by Return on Assets and dividend policy proxied by Dividend Payout Ratio and the dependent variable (Y) is Company Value proxied by Tobin's Q. The sample in this study was obtained by purposive sampling method. Based on the criteria and data processing process that have been set, 17 companies were determined as research samples. The data analysis technique used is multiple linear regression. The results of this study state that partially capital structure, profitability, and dividend policy have a positive and significant effect on company value. Simultaneously, the variables of capital structure, profitability and dividend policy have a significant effect on company value.